SANITATION AND DETOXIFICATION OF LAMA MEAT (LAMA GLAMA) INFECTED WITH SARCOCYSTIS AUCHENIAE THROUGH CHEMICAL METHODS: MARINATED, SMOKED, DRY CURED AND WET CURED - Granados Z., Lidia (2007)
The sanitation and disinfecting of lama meat naturally infected with macrocysts of Sarcocystis aucheniae through any of four chemical methods (marinated, smoked, dry cured and wet cured) was evaluated. In addition, a positive control group (non-treated meat) was included. A lisis of macrocysts from treated and non-treated meats was prepared and inoculated into 30 rabbits (100 μg/kg of body weigh, subcutaneously). Rabbits of the humid cured and positive control groups showed clinical signs of toxicity and died within 8-12 hours post-inoculation. Furthermore, 12 puppies of 4-6 months of age were fed with the infected lama meat (150-200 macrocysts per puppy) previously treated with one of the chemical methods under evaluation (one group was kept as a positive control one). Solely dogs of the positive control group eliminated sporocysts after 14 days of ingestion. The results showed that marinated, smoked and dry cured methods were able to clean and disinfect lama meat infected with macrocysts of Sarcocystis aucheniae.